Funções de pedotransferência e estrutura de variabilidade espacial da retenção de água em solos de várzea do Rio Grande do Sul - Nebel, Álvaro Luiz Carvalho (2009)
The understanding of the dynamics of the water in the soil-plant-atmosphere system, including the water availability to the crops, soil water infiltration, drainage and soil solute movement, depends on the knowledge of the relation between the soil water content and the matric potential, represented by the soil water retention curve (SWRC). However, the establishment of SWRCs is laborious and time consuming, besides being costly. A alternative is its estimate through statistical equations called Pedotransfer Functions (PTFs). The aim of this study was to evaluate the ability of some existing PTFs, in predicting the soil water retention and to capture its spatial variability structure, using geostatistical tools, when applied in a lowland soil of the south region of Brazil. For this, an experimental 10 x 10 m grid was established and soil disturbed and undisturbed samples were collected in the 0-0.20 m soil depth, totaling 100 experimental points. The following soil attributes were determined in each point: soil texture, soil organic carbon, pH, cation exchange capacity, soil bulk density, and the soil water retention curve. Eight developed PTFs for estimating gravimetric soil water content, eight for estimating volumetric water content and five for estimating the van Genuchten model parameters were evaluated using the statistical measures mean error (ME), and the root mean square error (RMSE). Results indicated that the Oliveira et al. (2002) PTF presented the best performance for estimating the gravimetric soil water content at the tension of 33kPa, with mean error (ME) value of 0.0136g.g-1, while for the gravimetric water content at tension of 1500kPa the Pidgeon (1972) FPT was the best, with ME value of -0,0054g.g-1. Concerning to the potential of describing the spatial variability structure the Bell & van Keulen (1995 and 1996) and of Urach (2007) PTFs presented the best performance based on the results from the cross validation technique. For estimating the soil water volumetric content at the tension of 10kPa the Tomasela et al. (2002) was the best (ME of 0.019cm3.cm-3), while Rawls et al. (1982) and van den Berg et al. (1997) PTFs were the best for estimating soil water content at the tension of 33kPa (ME of 0.001cm3.cm-3) and 1500kPa (ME of -0.008cm3.cm-3), respectively. The range and sill geostatistical parameters for the tension of 33kPa were reasonable estimated, while for the tension of 1500kPa they were underestimated by the evaluated PTFs. The Parametric Pedotransfer Function constructed by Vereecken et al.(1989) presented the lowest value of ME (0.0247cm3.cm-3), while the Hodnett and Tomasella (2002) PTF presented the lowest value of RMSE (0.0367 cm3.cm-3). Both PTFs well described the experimental semivariograms of the soil water content at the tensions of 10kPa and 33kPa, however their performance was not good for the tension of 1500kPa.